More frequent naps are associated with lower cognitive development in a cohort of 8–38‐month‐old children, during the Covid‐19 pandemic - Gliga, Teodora; Hendry, Alexandra; Kong, Shannon P.; Ewing, Ben; Davies, Catherine; McGillion, Michelle; Gonzalez‐Gomez, Nayeli (JCPP advances, 2023)
Background How often a child naps, during infancy, is believed to reflect both intrinsic factors, that is, the need of an immature brain to consolidate information soon after it is acquired, and environmental factors. Difficulty accounting for important environmental factors that interfere with a child's sleep needs (e.g., attending daycare) has clouded our ability to understand the role of intrinsic drivers of napping frequency. Methods Here we investigate sleep patterns in association with two measures of cognitive ability, vocabulary size, measured with the Oxford‐Communicative Development Inventory (N = 298) and cognitive executive functions (EF), measured with the Early EF Questionnaire (N = 463), in a cohort of 8–38‐month‐olds. Importantly, because of the social distancing measures imposed during the Covid‐19 Spring 2020 lockdown, in the UK, measures of sleep were taken when children did not access daycare settings. Results We find that children with more frequent but shorter naps than expected for their age had lower concurrent receptive vocabularies, lower cognitive EF and a slower increase in expressive vocabulary from spring to winter 2020, when age, sex, and SES were accounted for. The negative association between vocabulary and frequency of naps became stronger with age. Conclusions These findings suggest that the structure of daytime sleep is an indicator of cognitive development and highlight the importance of considering environmental perturbations and age when investigating developmental correlates of sleep. Frequent napping, in childhood, is believed to reflect an brain's need to consolidate information soon after learning, yet a previous study showed that more frequent napping associates with higher rather than lower cognitive development. During the UK Covid‐19 lockdown, closure of daycare removed one environmental factor that may interfere with children's sleep need. In a cohort of 8–38‐month olds followed up during lockdown, more frequent naps associated with lower concurrent vocabulary and executive functions. For example, still napping once a day, in children over 25 months old, is associated with lower vocabularies (see Figure).